The influence of transformational leadership on the relationship between an entrepreneurial mindset and corporate entrepreneurship - Govender, Thanusha (My University, 2016)
Although corporate entrepreneurship has been examined extensively and alike the antecedents of corporate entrepreneurship, have become a key interest to researchers. The examination of organisational and cognitive factors that drive corporate entrepreneurship is an area of study still in its infancy. This research report, aimed to bridge this knowledge gap, by evaluating the effect of transformational leadership and entrepreneurial mindset in enhancing levels of corporate entrepreneurship. This cross-sectional, empirical study is composed of 173 independent samples of management employees, taken from within a major African bank, headquartered in South Africa. The research, based on structural equation modelling, demonstrated that an entrepreneurial mindset and transformational leadership is positively related to higher levels of corporate entrepreneurship. Equally, empirical evidence was discovered, using structural equation modelling and regression analytics, that transformational leadership positively influences the behavioural relationship between the entrepreneurial mindset and corporate entrepreneurship. This occurs through the mediation causal relationship of transformational leadership, between both latent variables, and the bidirectional causal effect between transformational leadership and an entrepreneurial mindset.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation Johannesburg, 2016
Keywords: Leadership--South Africa; Entrepreneurship--South Africa